PECULIARITIES OF INHERITANCE IN THE CONDITIONS OF MARTIAL LAW IN UKRAINE - Timush, Iryna; Koval, Iolanta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to formulate proposals for improving the legal regulation of inheritance relations under martial law based on a scientific and practical analysis of the norms of the current legislation of Ukraine in the field of inheritance and social challenges. Research methods: the work uses general scientific and legal methods of cognition, namely: dialectical, formal-legal; system-structural, analysis and synthesis, modeling. Results: outlined features of inheritance under martial law; problems of the inheritance acceptance procedure were identified; changes in normative legal acts in the field of inheritance law were analyzed; deficiencies/gaps of legal regulation in the field of inheritance in the conditions of martial law were revealed; directions for improving the current legislation are proposed, taking into account the interests of servicemen and other members of formations participating in military operations. Discussion: in the conditions of martial law, the issue of obtaining inheritance needs to be studied, to respond to new challenges, and the right to inheritance requires additional guarantees; the main regulatory influence on inheritance relations under martial law occurs through a number of laws and by-laws, certain provisions of by-laws on inheritance contradict the laws. The authors note that the introduction of martial law on the territory of Ukraine affected the change in the legal regulation of inheritance relations, in particular, regarding the procedure for notarizing a will and accepting inheritance. It is problematic to improve inheritance procedures in changing and unstable social conditions in order to ensure the right of inheritance of servicemen and members of other formations who are in the combat zone, are in captivity of the enemy, convicted in the Russian Federation until serving their criminal sentence, and there are no missing persons. Inheritance under martial law requires further research in order to fill gaps in inheritance relationships. Despite the difficult challenges, since the beginning of the military aggression, a number of normative legal acts have been adopted, which define the specifics of the exercise of inheritance rights under martial law, thanks to which state and private notaries continue to perform notarial actions regarding inheritance.